2002
DOI: 10.1037/0735-7028.33.4.402
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary survey of counseling psychologists' personal experiences with depression and treatment.

Abstract: The fact that psychologists may not realize how much their own diagnosable emotional problems can impact their practices led to the undertaking of an exploratory survey of practicing psychologists in order to assess that notion. The results of a random sample of 1,000 psychologists indicate that women were more frequent respondents than men by a ratio of 3 to 2 and that depression (dysthymia) was the most frequently acknowledged diagnosis. Respondents felt that their emotional issues gave them more empathy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
144
4
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(160 citation statements)
references
References 30 publications
9
144
4
3
Order By: Relevance
“…In sum, our fi ndings suggest that personal therapy can benefi t novice therapists in that it may lead to a greater understanding in the goals and tasks of, as well confi dence in, the treatment process that they themselves coordinate. Gilroy, Carroll and Murra (2002) have even gone so far as to proclaim that 'it is imperative that personal psychotherapy be mandated' for trainees. However, as noted by Forrest and Elman (2005), such edicts may pose a threat to the confi dentiality of the student if boundaries are not well maintained between the program and treating therapists.…”
Section: Discussionmentioning
confidence: 97%
“…In sum, our fi ndings suggest that personal therapy can benefi t novice therapists in that it may lead to a greater understanding in the goals and tasks of, as well confi dence in, the treatment process that they themselves coordinate. Gilroy, Carroll and Murra (2002) have even gone so far as to proclaim that 'it is imperative that personal psychotherapy be mandated' for trainees. However, as noted by Forrest and Elman (2005), such edicts may pose a threat to the confi dentiality of the student if boundaries are not well maintained between the program and treating therapists.…”
Section: Discussionmentioning
confidence: 97%
“…Moderate to high levels of stress were observed in a sample of British clinical psychologists, and specifically, women and the less experienced, less socially supported participants reported greater psychological distress (Cushway & Tyler, 1996). Several theories have been proposed to account for the stress that helping professionals In addition to the occupational hazards they face, psychotherapists may lack adequate self-care practices that are critical to offset the effects of stress (Baker, 2003;Figley, 2002;Gilroy et al, 2002;Guy & Norcross, 1998;Skovholt, Grier, & Hanson, 2001). Among studies that have assessed practitioner selfcare, Mahoney (1997) found the most commonly used behaviors were reading for pleasure, exercising, taking vacations, having a hobby, supervising peers, and praying or meditating.…”
Section: Self-carementioning
confidence: 99%
“…Studies using more traditional epistemologies have reported that professionals with service user experience encounter dilemmas (Berry, Hayward, & Chandler, 2011;Cain, 2000;Charlemagne-Odle, Harmon, & Maltby, 2014;Gilroy, Carroll, & Murra, 2001;Stanley, Manthrope, & White, 2007;van Erp, Hendriksen-Favier, & Boer, 2010). These include issues regarding self-disclosure, experiencing stigma, prejudice and discrimination, being accused of overidentification and boundary violation, having reduced energy, confidence and emotional presence, and a discrepancy between their personal identity and their professional role.…”
Section: Introductionmentioning
confidence: 99%